Association between pacifier use and bottle-feeding and unfavorable behaviors during breastfeeding, - Batista,Christyann L.C. (2018)
Abstract Objective: To investigate the association between pacifier use and bottle-feeding and unfavorable behaviors during breastfeeding. Method: A cross-sectional study was conducted with 427 babies/mothers. Socio-demographic, perinatal data, and information about the use of artificial nipples (pacifier and/or bottle) were collected through a questionnaire. The breastfeeding aspects regarding position, affectivity, sucking behavior, baby responses, and breast anatomy were evaluated through observation during breastfeeding. The chi-squared test and the multiple linear regression analysis were used to investigate the association between the variables. Results: The aspects of breastfeeding that showed higher percentages of the category "poor" were sucking behavior (22.5%) and position (22.2%). The group of infants who used pacifiers and/or bottle showed higher percentages in the poor and fair categories when compared with the good category for all five breastfeeding aspects evaluated (p < 0.001). The linear regression analysis revealed that the increase in the number of unfavorable behaviors regarding position, affectivity, sucking behavior, and baby responses were independently associated with both pacifier and bottle use (β positive, p < 0.05), while breast anatomy was independently associated only with bottle use. Conclusion: The findings suggest that the use of pacifiers and/or bottle-feeding may be associated with unfavorable behaviors during breastfeeding, especially the use of bottle-feeding.